PERBANDINGAN PEMERIKSAAN GLUKOSA DARAH PUASA DENGAN MENGGUNAKAN SAMPEL SERUM DAN PLASMA EDTA PADA PASIEN DIABETES MELITUS TIPE 2 - Indrajati Puspita; Muhammad Rizki Kurniawan; Apriyani Riyanti (Journal of Indonesian Medical Laboratory and Science, 2023)
Diabetes mellitus is known as the Silent Killer because sufferers often don't realize its existence, and when random laboratory tests are carried out and there are complaints, it is realized that the patient has diabetes mellitus. This study was conducted to determine whether there is a significant difference in fasting blood glucose examination when using EDTA serum and plasma samples. In general, the sample used for this examination is serum, namely blood without anticoagulants or fresh blood (whole blood). The research method used observational analytical. Where serum and plasma EDTA are independent variables and fasting blood glucose as the dependent variable, using 30 test samples for fasting blood glucose examination in patients with type 2 Diabetes Mellitus. The results of the research conducted on fasting blood glucose examination with both test samples, it can be concluded that there is no significant difference in the results of fasting blood glucose test using EDTA serum and plasma samples.